Multinational companies in China : navigating the eight common management pitfalls - Guo, Xin, 1969-; Gallo, Frank T. (Emerald Publishing Limited, 2017)
This book explores some of the most common mistakes made by multinational companies doing business in China, in both cultural and managerial contexts. These shared mistakes could be as far-reaching as managing talent, local vs. global decision making, or could be as mundane as managing title, pay and performance. Many mistakes are rooted in a lack of understanding of the Chinese market in two areas: the unique talent and culture environment, and the immense opportunity potential. Very often, MNCs' global or local leaders lack the ability to make discretional decisions with one-size-fits-all approaches under the cloak of global consistency, or treating a China operation as one-of-the outfits (and a small one in the world revenue pool), even though they understand the market potential in theory. MNCs have enjoyed great success in China while many others have yet to realize their opportunities. China business continues to grow, and opportunities continue to develop. This book will guide business leaders on how to avoid the most common management pitfalls in China business, and will help the capitalize on the huge opportunity that remains in this region.